Translation and fantasy literature in Taiwan : translators as cultural brokers and social networkers - Chung, Yu-Ling; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This book examines the rise in popularity of fantasy literature in Taiwan and the crucial but often invisible role that translators have played in making this genre widely available. Topics covered include global fantasy fever, Chinese fantasy, game industry, the social status of translators, and the sociological direction of translations studies.
Keywords: Linguistics; Literature -- Translations; Applied linguistics; Philology; Sociolinguistics; Translation and interpretation; Language and languages -- Style; Linguistics; Applied Linguistics; Sociolinguistics; Stylistics; Translation; Translation Studies; Language and Literature